FTO (fat-mass and obesity-associated protein) deficiency aggravates age-dependent depression-like behaviors and cognitive impairment - Mengdie Li; Yating Yang; Tangcong Chen; Yueyang Luo; Yingqian Zhang; Huanzhong Liu; Michael Maes (Behavioral and Brain Functions)
Abstract Background The demethylase fat mass and obesity-related associated protein (FTO) is strongly associated with depression. Aging is a risk factor for synaptic plasticity damage in the brain and leads to neurocognitive dysfunctions. FTO-dependent m6A modification plays an important role in neurodevelopment and cognitive function. However, whether FTO is associated with susceptibility to depression in different age groups remains unknown. Methods We subjected 3-and 12-month-old C57BL/6J male mice to chronic unpredictable mild stress (CUMS) for 6 weeks, of which 3 weeks were used for hippocampal injection of FTO knockdown adeno-associated virus 9 shRNA (FTO-KD AAV9). Finally, 36 male mice in each 3-month-old and 12-month-old groups were divided into three groups (n = 12): Sham, CUMS, and FTO-KD. After 6 weeks, we assessed behavioral deficits (depressive and anxiety-like behaviors and cognitive impairment) by behavioral tests and hippocampal neuronal damage (dendritic spine density, neuronal atrophy, and expression of proteins associated with synaptic plasticity) by molecular biochemical experiments. Results The results showed that 12-month-old C57BL/6J mice were more likely to develop depression-like behavior and spatial learning and memory impairment induced by CUMS than 3-month-old mice. Chronic stress-induced depression-like behavior and cognitive impairment worsened after the FTO-KD intervention. In the hippocampus of 3- and 12-month-old mice, CUMS induced the downregulation of FTO, nerve growth factor (NGF), reelin, and synaptic plasticity-related proteins. It also caused abnormal brain-derived neurotrophic factor (BDNF)- the tropomyosin-related kinase B (TrkB) signaling, reduced density of dendritic spines, and an increased number of neuronal pyknotic nuclei, leading to neuronal disarray, which was more significant in 12-month-old animals. FTO deficiency accelerated neuronal damage in the hippocampus of 12-month-old CUMS mice. Conclusions This study provides rodent evidence that FTO deficiency may increase the susceptibility to depression in older adults by impairing hippocampal neuronal function and neuronal synaptic plasticity in an age-dependent manner. This suggests that the development of FTO activators may be an effective treatment for depression in older adults.